IMPLEMENTATION OF CRYPTOGRAPHY TECHNIQUES IN CLOUD COMPUTING - Bansal, Shaffy; Bhardwaj, Vijay (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is the set of IT services that are provided by cloud service provider to the users over the Internet. It is Pay-per-use for On-demand service. The main concern of the cloud computing is Security. In this paper, studies the basics of cloud computing and two main encryption/decryption algorithms that are AES (Advanced Encryption Standard) and DES (Data Encryption Standard). The paper shows the implementation of AES and DES algorithms for the conversion of Plaintext to Cipher text.